Digteren og den sandheds ånd. Grundtvigs helligåndsteologi og den engelske romantik - Wigh-Poulsen, Henrik (Grundtvig-studier, 1991)
The Poet and the Spirit of Truth. - Grundtvig’s theology of The Holy Spirit and the English Romanticism By Henrik Wigh-Poulsen. Like his English contemporary, the romantic poet William Wordsworth, Grundtvig sees himself as belonging to the elect company of poet-prophets, the gifted and visionary seers, who by means of their imagination, are capable of reading God’s signature in nature.But in spite of this shared romantic trait there is a marked difference between Wordsworth and Grundtvig in their shared predilection for the windmetaphor. Whereas Wordsworth’s inspiring, creative .gentle breeze., according to the literary critic M.H. Abrams, is a distant secularized and naturalized relative to The Holy Spirit, Grundtvig’s .spiritual waft. is the rushing wind of the Pentecost itself. It is this ‘ Spirit of Truth’ that descends on nature and in nature bears witness to the paradisal; but also, at the same time, qualifies the poet as a true, Christian poet.As a poet-prophet committed exclusively to The Holy Spirit, Grundtvig becomes a rather isolated figure, vulnerable to his own doubt, whether he, in his poetry, is truly inspired or just the victim of his own private and deceitful imagination. Repeatedly he confronts himself with this doubt, repents, states his unworthiness and finally settles with the conviction, that, in his poetic vocation, he is elected by the Spirit itself.‘ The Unparalleled Discovery’, however, seems to cause a growing poetic and prophetic self-confidence in Grundtvig’s writings. His newly gained sense of a real, historical foundation of the church diminishes his desperate sense of isolation and fear of haughtiness and subjectivity, and it enables him to speak louder and more freely in the service of the Spirit. Finally, as the community of Grundtvig, the poet-prophet, emerges as a real, living and visible community, his anxiety of his imagination polluting the .spiritual waft., disappears, and as a fullgrown romantic poet and hymnwriter he gives himself fully to the breath, the waft, the mighty rushing wind of the Pentecost.